Biometrics in Network Security - Fathima, Noor; Pallavi, BN; Kavitha, Kavitha (International Journal of Computer Sciences and Engineering, 2025)
— Security has been a major interest for authentication over networking. In this modern society, mobile devices have a pertained importance with hundreds and millions users. With the help of pins, passwords there are weak authentication mechanisms which allow attackers to access the stored data. By implementing various methods for key exchange cryptographic can solve the problem of security. Identity verification is a developing and mesmerizes much attention. Biometric recognition mainly relates to the automatic recognition of individuals based on their behavioral characteristics. Almost appropriate is based on vein pattern is an approach that uses the vast network of blood vessels that lie underneath a skin. Vein pattern are unique and also difficult to duplicate even twin has an unlike and unique vein structure. Biometric security devices measure unique characteristics of a person, such as voice pattern, the iris or retina pattern of the eye and finger print. In biometrics, it is very difficult for someone to break into a system. Biometric security is a mechanism which is used to prove and provide access to a facility or system based on the automatic and direct verification of a single person’s physical behavior.